Impact of baseline blood pressure on the magnitude of blood pressure lowering by nifedipine gastrointestinal therapeutic system: refreshing the Wilder’s principle - Hu HJ; Zhang JD; Wang Y; Tian ZJ; Liu DM; Zhang GM; Gu GQ; Zheng HM; Xie RQ; Cui W (Dove Medical Press, 2017)
Haijuan Hu, Jidong Zhang, Yan Wang, Zejun Tian, Demin Liu, Guangming Zhang, Guoqiang Gu, Hongmei Zheng, Ruiqin Xie, Wei Cui Department of Cardiology, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China Background: The objective of the study was to investigate the relationship between baseline blood pressure (BP) and the magnitude of BP reduction in patients with essential hypertension treated with nifedipine gastrointestinal therapeutic system (NGTS).Methods and patients: One hundred and thirty-eight patients with essential hypertension were enrolled in this prospective, single-arm, open-label study. NGTS was administered for 24 weeks to achieve target BP of 140/90 mmHg. The dose could be uptitrated to 60 mg/d in case of unsatisfactory BP reduction after 4-week treatment. Home blood pressure measurement was recorded through the initial 1–14 days, and office BP and heart rate were evaluated at 2, 4, 8, 12, and 24 weeks.Results: One hundred and seventeen patients (84.8%) completed the study, and their average BP decreased by 19.0/11.3 mmHg after 24 weeks. The reduction of either systolic or diastolic BP was positively correlated with baseline BP at weeks 2, 4, or 24 after treatment (r=0.603–0.762, all p<0.05). The maximal BP reduction was observed in 83% of patients at 4 weeks of treatment even though the dose of nifedipine remained unchanged (30 mg/day).Conclusion: These findings show that BP reduction is greatly influenced by the baseline level. Patients with high baseline BP had maximum reduction after treatment with NGTS, and the maximal antihypertensive efficacy of NGTS could appear even at 4 weeks after treatment initiation. Keywords: baseline blood pressure, hypertension, nifedipine gastrointestinal therapeutic system